Computational study of cis-oleic acid adsorption on Ni(1 1 1) surface - Simonetti, Sandra Isabel (2012)
In the present work, the Atom Superposition and Electron Delocalization method has been applied in order to study the adsorption of cis-oleic acid on Ni(1 1 1) surface. This molecule presents two active functional groups, C=C (in the middle) and -COOH (at one end). Therefore, it is important to explore adsorption on the metal surface through the C=C bond in a geometry parallel to the surface and also in a vertical one with COOH pointing at Ni atoms. Our results indicate that the parallel geometry is more stable than the vertical one and C=C bond adsorption dominates the process. Energetic results show a strong interaction with the metallic surface. Ni-Ni, C=C, and C-C bonds are weakened upon adsorption because of a bonding interaction between carbons and nickel surface. We found that Ni 5d z 2 and 5d yz orbitals play an important role in the bonding between C p x , p z orbitals and surface, and the same happens with Ni 6p x and Ni 6p z . A small NiH interaction is also detected. © 2012 Elsevier B.V. All rights reserved.